MAKNA DAN INTERAKSIONALISME SIMBOLIK DALAM TRADISI GENDUREN DI BLITAR JAWA TIMUR: (STUDI LIVING HADIS) - Sukmani; Repa Hudan Lisalam (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2024)
Currently, more and more people believe in the power of the environment and nature, including the sun, the mountain atmosphere, and ancestral spirits. The purpose of this study is to examine the values, symbolic meanings, history, and implementation process of the Genduren tradition. Examining the relationship between the concept of living traditions and the social and spiritual benefits felt by the community from customs is also another objective of this study. This research uses qualitative and ethnographic methodologies. George Herbert Mead refers to symbolic interactionism as social interaction facilitated by symbols. The meaning of symbols can shape social interaction. An example of symbolic interactionism theory in everyday life is when a waiter sells various items in a store. Blitar, East Java, illustrates how symbols represent certain values that are highly valued by the community. In addition, this interaction leads to new habits or habits that are carried out regularly with the same purpose. The author concludes the research problem formulation by observing passive participation and asking for opinions from several informants who deeply understand the genduren tradition. Translated with DeepL.com (free version)